Curing agent for iron tailing engineering backfill material and use method of curing agent

By designing a curing agent containing silicate cement, calcium hydroxide, fly ash, modified slag micro powder, alkali slag and sodium phosphate buffer system, the problem of inconsistent performance of curing agents in the prior art under different geological conditions is solved, and the stable performance and high adaptability in complex environments are achieved.

CN119683928AInactive Publication Date: 2025-03-25NANJING BODA ENVIRONMENTAL TECH CO LTD

Patent Information

Application Number
CN202411829617.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The curing agents of existing iron tailings backfill materials are inconsistent under different geological conditions, especially in temperature changes and complex environments, the strength and durability of the material are difficult to maintain stability.

Method used

A curing agent for backfill materials for iron tailings engineering was designed, including silicate cement, calcium hydroxide, fly ash, modified slag micro powder, alkali slag and sodium phosphate buffer systems. Through the synergistic action of these components and the adjustment of the sodium phosphate buffer system, the self-regulation and stable performance of the curing agent to the environment is achieved.

Benefits of technology

The curing agent can maintain stable performance under different environmental conditions, improve construction flexibility, reduce construction risks, and significantly improve the adaptability and application range of cured materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185246930000101
    Figure BDA0005185246930000101
  • Figure BDA0005185246930000111
    Figure BDA0005185246930000111
Patent Text Reader

Abstract

The invention relates to a curing agent for an iron tailing engineering backfill material and a use method of the curing agent. The curing agent is composed of Portland cement, calcium hydroxide, fly ash, modified superfine slag powder, alkaline residues and a sodium phosphate buffer system. And by adding the curing agent, the backfill material has excellent compressive strength, durability and permeability resistance. Due to the filling and interface enhancing effects of the modified superfine slag powder, the compactness of the material is remarkably improved, and the porosity and the permeability coefficient are reduced; the alkaline residues accelerate the curing reaction, and the freeze-thaw resistance of the material is improved. The method is suitable for various complex geological and environmental conditions, and the stability and safety of the backfill material in an extreme environment are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a curing agent for iron tailings engineering backfill material and a use method thereof, belonging to the technical field of curing agents. Background Art

[0002] The solidification technology of iron tailings backfill materials has gradually become an important research direction with the growing demand for mine waste treatment and resource recycling. Traditionally, the development of curing agents has focused on improving the compressive strength, durability and impermeability of materials to ensure their safety and stability in geological engineering. Commonly used curing agents include cement, lime and various chemical additives, which are physically or chemically combined with tailings particles to form a solid structure. However, as the requirements for adaptability of engineering projects to different geological conditions increase, curing materials need to have higher flexibility and environmental adaptability to cope with different temperatures and chemical environments. This requirement is particularly applicable to projects in complex mining environments and extreme climatic conditions. The curing agent must not only have basic strength properties, but also maintain a stable curing effect under diverse environmental conditions.

[0003] A Chinese patent (publication number: CN116217164A) discloses an inorganic high-strength fast curing agent, including the following raw materials in parts by weight: 30-50 parts of silicate cement; 3-6 parts of wollastonite powder; 3-5 parts of quicklime; 1-3 parts of alumina; 3-5 parts of fly ash; 30-50 parts of iron tailings; 0.5-1.5 parts of potassium hydroxide; 3-5 parts of steel slag; 0.5-1.5 parts of sodium sulfate; according to the properties and composition of the iron tailings, silicate cement and quicklime are selected to react with them to obtain a curing agent that can prepare high-strength products; it is convenient to obtain materials and has low cost. The shortcomings of the prior art are mainly reflected in the fact that the adaptability of the curing agent to the environment is not considered, resulting in inconsistent performance under different geological conditions. In an environment where the temperature changes, the curing reaction of the traditional curing agent may be inhibited or accelerated, resulting in fluctuations in the strength and durability of the final material. In addition, the existing curing agents often rely on a single chemical reaction mechanism and cannot maintain the expected performance in certain complex environments, such as low-temperature soil. This shortcoming limits the widespread application of tailings backfill materials, and our invention aims to solve this problem by designing a curing agent that is sensitive to specific environmental conditions. The curing agent can self-regulate according to environmental factors such as temperature and optimize the curing process, so that it can maintain stable performance in various complex environments, thereby improving construction flexibility and reducing construction risks. This innovative direction significantly improves the adaptability and application range of curing materials, and provides a new technical approach for the efficient utilization of iron tailings. Summary of the invention

[0004] To solve the technical problems existing in the prior art, the present application provides a curing agent for backfill materials of iron tailings engineering, which includes, by mass: 30 to 40 parts of silicate cement, 5 to 10 parts of calcium hydroxide, 15 to 25 parts of fly ash, 1 to 3 parts of modified slag powder, 0.5 to 2 parts of alkaline slag and 1 to 3 parts of sodium phosphate buffer system.

[0005] It should be noted that silicate cement provides a basic gelling effect to generate hydration products to fill pores and enhance strength; calcium hydroxide and fly ash further enhance the hydration reaction to generate more calcium silicate hydrate, thereby enhancing compressive strength and acid and alkali resistance; modified slag powder significantly improves the density of the material, and improves its freeze-thaw resistance and acid and alkali resistance; alkaline slag accelerates the hardening of the material and improves its freeze-thaw resistance; the sodium phosphate buffer system enhances the chemical stability of the material by adjusting the pH value, ensuring good durability in acid and alkali environments.

[0006] As a preferred technical solution for a curing agent for backfill materials in iron tailings engineering, the invention comprises, by mass, 35 parts of silicate cement, 7 parts of calcium hydroxide, 20 parts of fly ash, 2 parts of modified slag powder, 1 part of alkaline slag, and 2 parts of sodium phosphate buffer system.

[0007] As a preferred technical solution for a curing agent for backfill materials in iron tailings engineering, the sodium phosphate buffer system consists of monobasic sodium phosphate and dibasic sodium phosphate.

[0008] It should be noted that under acidic conditions, the alkalinity of dibasic sodium phosphate can effectively neutralize external acidic substances and prevent the cement-based components (such as Ca(OH)2) in the material from being corroded by acid. The sodium phosphate buffer system allows the material to maintain a high alkalinity under a low pH environment, enhancing the material's acid resistance; in an alkaline environment, the monobasic sodium phosphate in the sodium phosphate buffer system can release hydrogen ions to offset excessive alkaline substances (such as OH - ) to prevent the structural instability of the material due to excessive alkalinity, especially in alkaline water and soil environments, where the buffer system plays a balancing role to prevent excessive alkalinity from corroding the material.

[0009] As a preferred technical solution for a curing agent for iron tailings engineering backfill materials, the preparation steps of the modified slag powder include:

[0010] Slowly add the dried nano-scale slag powder into anhydrous ethanol, mix it with ultrasonic equipment, weigh an appropriate amount of organosilane coupling agent, slowly add it into the dispersion, keep stirring, control the reaction temperature at 40 to 80°C, and continue stirring for 1-2 hours, filter the reaction liquid through a vacuum filter, retain the modified slag powder, wash the slag powder with anhydrous ethanol solvent, remove the residual organosilane and by-products. Repeat washing 3-5 times, put the washed slag powder into an oven, and dry it at 80-100°C for 12-24 hours.

[0011] It should be noted that the preparation of the modified slag powder is to functionalize the surface of the nano-slag powder by a condensation reaction between an organic silane coupling agent and the surface of the nano-slag powder, thereby giving it better compatibility and reactivity with organic materials. The modification process includes steps such as ultrasonic dispersion, coupling agent reaction, vacuum filtration, washing and drying, which together ensure that the surface modification of the nano-slag powder is sufficient and uniform. The modified nano-slag powder has enhanced dispersibility, chemical stability and reactivity, and can significantly improve the performance of materials in various material systems, such as enhancing the strength, durability and freeze-thaw resistance of composite materials.

[0012] As a preferred technical solution for a curing agent for iron tailings engineering backfill materials, the organosilane coupling agent is 3-aminopropyltriethoxysilane, and the organosilane coupling agent accounts for 1wt% to 3wt% of the mass of the nano-scale slag powder.

[0013] It should be noted that the ethoxy group of APTES reacts with the surface silanol (Si-OH) of nano-slag powder through hydrolysis to generate a stable silicon oxygen bond (Si-O-Si), so that APTES is firmly bound to the surface of nano-slag powder. At the same time, the amino group in the APTES molecule can form hydrogen bonds or covalent bonds with the organic components (such as polymers) or inorganic components (such as cement matrix) of the backfill material, thereby significantly improving the interfacial bonding between the nano-slag powder and the matrix material. This enhanced interfacial bonding can effectively resist the interface detachment or crack propagation caused by temperature changes when the material is subjected to freeze-thaw cycle stress, thereby improving the material's anti-freeze-thaw performance, and this enhanced interfacial bonding reduces the pores between the nanoparticles and the matrix, thereby improving the material's density. The reduction in porosity means that the water or gas permeation path in the material is reduced, and the permeability is significantly reduced.

[0014] In addition, the method for using the curing agent prepared by the present application and added to the backfill material of the iron tailings engineering includes the following technical steps:

[0015] Step 1. gradually add the stirred curing agent to the iron tailings and steel slag according to the proportion, and stir for 5 to 10 minutes by a stirrer; wherein the added amount of the curing agent is 10wt%-30wt% of the iron tailings, and the added amount of the steel slag is 5wt%-10wt% of the iron tailings;

[0016] Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio (W / C) between 0.3-0.5.

[0017] As a preferred technical solution for the use of a solidifying agent, the iron tailings include: 40 to 50 parts of large particles, 30 to 40 parts of medium particles and 10 to 20 parts of small particles; the large particles are particles with a particle size greater than 500 microns, the medium particles are particles with a particle size between 100 and 500 microns, and the small particles are particles with a particle size less than 100 microns.

[0018] It should be noted that the particles in the iron tailings are divided into large particles (>500 microns), medium particles (100-500 microns) and small particles (<100 microns) according to their particle size. By mixing them in a reasonable proportion, the density of the material can be significantly improved. Large particles provide skeleton support in the mixture, medium particles fill the gaps between large particles, and small particles further fill the tiny pores between medium particles. This optimized distribution of multi-scale particles not only reduces the porosity of the material, but also improves the compressive strength and durability, while reducing the permeability coefficient, making the material show excellent stability in engineering applications. The role of the curing agent is that its effective ingredients can penetrate between the particles of iron tailings and steel slag, react chemically with the surface of the particles, and generate hydration products such as hydrated calcium silicate. These products can fill the pores between the particles, further increase the density of the material, and improve the mechanical strength of the material. In addition, the curing agent can accelerate the curing reaction, help the material to quickly set during the construction process, and meet the requirements of engineering strength. The control of the water-cement ratio plays a key role in the performance of the material. By controlling the water-cement ratio between 0.3-0.5, excess pore water can be reduced, excessive voids can be avoided in the material, and the compressive strength and impermeability of the material can be further improved. A reasonable water-cement ratio makes the microstructure of the material more compact, thereby improving its overall performance. A too high water-cement ratio may increase the porosity of the material, resulting in a decrease in strength. The synergistic effect of steel slag and iron tailings also plays an important role. 5%-10% of steel slag is added, and the Ca(OH)2 generated by C2S and C3S in the steel slag during the hydration process can react with the active silica and alumina in the iron tailings to form additional CSH gel and hydrated calcium aluminate (CAH). These gel products have good gelling properties, can fill the pores of the material, improve density, and enhance mechanical strength. Therefore, through the optimization of the above steps, the backfill material has been significantly improved in strength, durability and impermeability, ensuring the long-term stability and safety of the project.

[0019] The beneficial effects of this application are mainly reflected in the following aspects:

[0020] 1. Improve the strength and durability of backfill materials: By using a combination of multiple components such as silicate cement, calcium hydroxide, fly ash and modified slag powder, a large amount of hydration products are generated to fill the pores, enhancing the compressive strength and crack resistance of the material. The synergistic effect of these components enables the backfill material to maintain high strength and durability under complex geological conditions, especially in extreme environments such as low temperature or acidic and alkaline soils.

[0021] 2. Reduce the porosity and permeability of materials: Modified slag powder has a good filling effect, which can reduce the number of large pores and interconnected pores in the material, significantly reduce the porosity and permeability, and thus improve the density and anti-permeability of the material. This is very beneficial for use in engineering environments with large groundwater flows, reducing the intrusion of water and extending the service life of the material.

[0022] 3. Accelerate the curing reaction and improve construction efficiency: Adding alkali slag can promote the hydration reaction in cement, shorten the setting time of the material, increase the hardening speed, and enhance the anti-freeze and thaw performance, thereby speeding up the construction progress, which is especially suitable for engineering projects with tight construction period.

[0023] 4. Strong environmental adaptability: By adding a sodium phosphate buffer system, the backfill material can maintain a stable pH value in acidic and alkaline soils, preventing the material from being eroded by acid and alkali, and ensuring its durability in different environments.

[0024] 5. Optimize particle distribution and improve material density: The reasonable distribution of large, medium and small particles in iron tailings not only improves the mechanical properties of the material, but also reduces the pores through the filling effect between particles, thereby improving the stability and compressive resistance of the material. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0028] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0029] Preparation example of modified slag powder

[0030] The following is an explanation using Preparation Example 1 as an example.

[0031] The preparation steps of the modified slag powder in this preparation example include: slowly adding the dried nano-scale slag powder to anhydrous ethanol, mixing it with an ultrasonic device, weighing 3-aminopropyl triethoxysilane according to 1wt% of the mass of the nano-scale slag powder, slowly adding it to the dispersion, while keeping stirring, controlling the reaction temperature at 60°C, and stirring for 1 hour, filtering the reaction solution through a vacuum filtration device, retaining the modified slag powder, washing the slag powder with anhydrous ethanol solvent, and removing residual organosilane and by-products. Repeat the washing 3 times, put the washed slag powder into an oven, and dry it at 100°C for 24 hours.

[0032] Example

[0033] The iron tailings in the following embodiments are composed of large particles, medium particles and small particles. The large particles are particles with a particle size greater than 500 microns, the medium particles are particles with a particle size between 100 and 500 microns, and the small particles are particles with a particle size less than 100 microns.

[0034] Example 1

[0035] The curing agent for backfill materials of iron tailings engineering is prepared according to the following mass parts: 35 parts of silicate cement, 7 parts of calcium hydroxide, 20 parts of fly ash, 8 parts of modified slag powder (using the modified slag powder in Preparation Example 1), 1 part of alkaline slag and 2 parts of sodium phosphate buffer system; the sodium phosphate buffer system is composed of monobasic sodium phosphate and dibasic sodium phosphate.

[0036] Preparation of backfill material for iron tailings: Step 1. Add the stirred curing agent gradually into the iron tailings and steel slag in proportion, and stir for 5 minutes with a stirrer; wherein the added amount of the curing agent is 30wt% of the iron tailings, and the added amount of the steel slag is 5wt% of the iron tailings; the iron tailings includes: 50 parts of large particles, 30 parts of medium particles and 20 parts of small particles.

[0037] Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio (W / C) at 0.5.

[0038] Example 2

[0039] The curing agent for backfill materials of iron tailings engineering is prepared according to the following mass parts: 30 parts of silicate cement, 10 parts of calcium hydroxide, 20 parts of fly ash, 6 parts of modified slag powder (using the modified slag powder in Preparation Example 1), 1 part of alkaline slag and 2 parts of sodium phosphate buffer system; the sodium phosphate buffer system is composed of monobasic sodium phosphate and dibasic sodium phosphate.

[0040] Preparation of backfill material for iron tailings: Step 1. Add the stirred curing agent gradually into the iron tailings and steel slag in proportion, and stir for 5 minutes with a stirrer; wherein the added amount of the curing agent is 30wt% of the iron tailings, and the added amount of the steel slag is 5wt% of the iron tailings; the iron tailings includes: 50 parts of large particles, 30 parts of medium particles and 20 parts of small particles.

[0041] Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio (W / C) at 0.5.

[0042] Example 3

[0043] The curing agent for backfill materials of iron tailings engineering is prepared according to the following mass parts: 35 parts of silicate cement, 8 parts of calcium hydroxide, 25 parts of fly ash, 7 parts of modified slag powder (using the modified slag powder in Preparation Example 1), 0.5 parts of alkali slag and 1 part of sodium phosphate buffer system; wherein the sodium phosphate buffer system is composed of monobasic sodium phosphate and dibasic sodium phosphate.

[0044] Preparation of backfill material for iron tailings: Step 1. Gradually add the stirred curing agent to the iron tailings and steel slag in proportion, and stir for 5 minutes with a stirrer; wherein the added amount of the curing agent is 30wt% of the iron tailings, and the added amount of the steel slag is 5wt% of the iron tailings; the iron tailings includes: 35 parts of large particles, 40 parts of medium particles and 15 parts of small particles.

[0045] Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio (W / C) at 0.4.

[0046] Example 4

[0047] The curing agent for backfill materials of iron tailings engineering is prepared according to the following mass parts: 40 parts of silicate cement, 5 parts of calcium hydroxide, 15 parts of fly ash, 1 part of modified slag powder (using the modified slag powder in Preparation Example 1), 2 parts of alkali slag and 3 parts of sodium phosphate buffer system; the sodium phosphate buffer system is composed of monobasic sodium phosphate and dibasic sodium phosphate.

[0048] Preparation of backfill material for iron tailings: Step 1. Add the stirred curing agent to the iron tailings and steel slag gradually according to the proportion, and stir for 10 minutes by a stirrer; wherein the added amount of the curing agent is 20wt% of the iron tailings, and the added amount of the steel slag is 10wt% of the iron tailings; the iron tailings includes: 40 parts of large particles, 20 parts of medium particles and 10 parts of small particles.

[0049] Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio (W / C) at 0.3.

[0050] Examples 5 to 11

[0051] The difference between Examples 5 to 11 and Example 4 is that the added amounts of modified slag powder are different, as shown in Table 2 below.

[0052] Table 2

[0053]

[0054] Comparative Example 1

[0055] The difference between this control example and implementation 1 is that an equal amount of water is used to replace the alkali residue.

[0056] Comparative Example 2

[0057] The difference between this control example and implementation 1 is that an equal amount of nano-scale slag powder is used to replace the modified slag powder.

[0058] Performance Testing Methods

[0059] 1. The freeze-thaw resistance of the iron tailings engineering backfill material prepared using the curing agent prepared in this application was tested in accordance with GB / T50082-2009.

[0060] 2. The porosity and anti-permeability properties of the iron tailings engineering backfill material prepared using the curing agent prepared in this application were tested in accordance with GB / T50081-2019.

[0061] Table 3

[0062]

[0063] In combination with Examples 1 to 3 and Table 3, it can be seen that the compressive strength loss rate, mass loss rate, porosity and permeability coefficient of the iron tailings engineering backfill material prepared using the curing agent prepared in the present application are 8.54% to 9.86%, 2.45% to 3.12%, 6.53% to 7.56% and 1.5 to 2.5%, respectively. The iron tailings engineering backfill material prepared using the curing agent prepared in the present application has good freeze-thaw resistance, good anti-permeability and low porosity.

[0064] It can be seen from Example 1, Control Example 1 and Table 3 that when the curing agent prepared in the present application contains alkali slag, the compressive strength loss rate, mass loss rate, porosity and permeability coefficient of the iron tailings engineering backfill material are reduced. This may be because the alkaline components in the alkali slag react with the silicon-aluminum minerals in the iron tailings to generate hydrated silicates and other gel phases. These new phases can significantly enhance the structural strength of the material. The particles of the alkali slag can fill the tiny pores in the backfill material and reduce the porosity, thereby improving the density of the material and reducing the compressive strength loss rate. In addition, the alkali slag can also promote the hydration reaction, accelerate the curing process, reduce early mass loss, and improve long-term strength.

[0065] It can be seen from Example 1, Control Example 2 and Table 3 that when the curing agent prepared in the present application contains unmodified nano-slag powder, the compressive strength loss rate, mass loss rate, porosity and permeability coefficient of the iron tailings engineering backfill material are reduced. This may be because the amino group in the APTES molecule can form hydrogen bonds or covalent bonds with the organic components (such as polymers) or inorganic components (such as cement matrix) of the backfill material, thereby significantly improving the interfacial bonding force between the nano-slag powder and the matrix material. When the material is subjected to freeze-thaw cycle stress, this enhanced interfacial bonding force can effectively resist the interface detachment or crack propagation caused by temperature changes, thereby improving the material's anti-freeze-thaw performance, and this enhanced interfacial bonding reduces the pores between the nanoparticles and the matrix, thereby improving the material's density. The reduction in porosity means that the water or gas permeation path in the material is reduced, and the permeability is significantly reduced.

[0066] Combining Examples 4 to 11 and Table 3, it can be seen that as the content of modified slag powder gradually increases, the compressive strength loss rate and the mass loss rate gradually decrease. When the addition amount of modified slag powder reaches 6 parts, the compressive strength loss rate and the mass loss rate gradually tend to balance. This may be because the surface of the nano-scale slag powder can form a stronger interface bond with the matrix material (such as cement or other gelling materials) after modification. This enhanced interface bonding force effectively reduces the interface weakness between the particles and the matrix material, thereby improving the overall mechanical properties of the material, thereby improving the freeze-thaw resistance of the backfill material. At low addition amounts, with the increase of nano-slag powder, the interface reinforcement effect is significant, and the compressive strength loss rate and mass loss rate are significantly reduced. When the addition amount reaches 6, the interface reinforcement effect gradually tends to saturation, so the changes of the two begin to stabilize; with the gradual increase of the content of modified slag powder, the porosity and permeability coefficient gradually decrease. This may be because the filling effect of nano-slag powder not only reduces the number of large pores, but also reduces the volume of connected pores, thereby enhancing the density of the material, which causes the porosity and permeability of the material to gradually decrease with the increase of nano-slag powder addition.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A curing agent for backfill materials of iron tailings engineering, characterized in that: In terms of mass proportions, it includes: 30 to 40 parts of Portland cement, 5 to 10 parts of calcium hydroxide, 15 to 25 parts of fly ash, 6 to 8 parts of modified slag powder, 0.5 to 2 parts of alkali slag and 1 to 3 parts of sodium phosphate buffer system.

2. The curing agent for iron tailings engineering backfill material according to claim 1, characterized in that: The components include, by mass: 35 parts of silicate cement, 7 parts of calcium hydroxide, 20 parts of fly ash, 7 parts of modified slag powder, 1 part of alkaline slag, and 2 parts of sodium phosphate buffer system.

3. The curing agent for iron tailings engineering backfill material according to claim 1, characterized in that: The sodium phosphate buffer system consists of monobasic sodium phosphate and dibasic sodium phosphate.

4. The curing agent for iron tailings engineering backfill material according to claim 1, characterized in that: The preparation steps of the modified slag powder include: Slowly add the dried nano-scale slag powder into anhydrous ethanol, mix it using ultrasonic equipment, weigh an appropriate amount of organosilane coupling agent, slowly add it into the dispersion, and keep stirring. The reaction temperature is controlled at 40 to 80°C, and stirring is continued for 1-2 hours. Filter the reaction solution through a vacuum filtration device, retain the modified slag powder, wash the slag powder with anhydrous ethanol solvent, remove residual organosilane and by-products, and wash repeatedly for 3-5 times. Put the washed slag powder into an oven and dry it at 80-100°C for 12-24 hours.

5. The curing agent for iron tailings engineering backfill material according to claim 4, characterized in that: The organosilane coupling agent is 3-aminopropyltriethoxysilane, and the organosilane coupling agent accounts for 1wt% to 3wt% of the mass of the nano-scale slag powder.

6. The method for using the curing agent according to claim 1, characterized in that: The technical steps include: Step 1. gradually add the stirred curing agent to the iron tailings and steel slag according to the proportion, and stir for 5 to 10 minutes by a stirrer; wherein the added amount of the curing agent is 10wt%-30wt% of the iron tailings, and the added amount of the steel slag is 5wt%-10wt% of the iron tailings; Step 2. Add appropriate amount of water for wet mixing, and control the water-cement ratio between 0.3-0.

5.

7. The method for using a curing agent according to claim 1, characterized in that: The iron tailings include: 40 to 50 parts of large particles, 30 to 40 parts of medium particles and 10 to 20 parts of small particles.

8. The method for using a curing agent according to claim 7, characterized in that: The large particles are particles with a particle size greater than 500 microns, the medium particles are particles with a particle size between 100 and 500 microns, and the small particles are particles with a particle size less than 100 microns.

Citation Information

Patent Citations

  • Iron tailing curing agent and use method thereof

    CN116217164A

Cited By

  • Method for preparing solidified soil based on iron ore tail mud

    CN120097700A

  • A method for preparing a solidified soil based on iron ore tailings

    CN120097700B